USE OF THE PROBLEM SOLVING METHODIN THE EDUCATION OF STUDENTS TO DEVELOP COMMUNICATION SKILLS AT THE LESSONS OF A FOREIGN LANGUAGE - Elena S. Stepanova; Nadegda K. Studennikova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article focuses on the problem of students’ education to develop communication skills with the use of the problem solving method at the lessons of a foreign language. The question of understanding the problem solving method in the process of students’ education with the involvement of different points of view of famous scientists in this field is considered. It is stated that the problem solving method is closely connected with the group one as acquiring of communication skills can’t be abstract, it is definitely aroused by the interest to this or that problem. Group communication is considered to be the basic form of organization of studies to enhance communication and lexical and grammatical skills. The role of students’ independent work in the process of enhancing their communication skills is determined. It is pointed out that the use of supporting teaching resources such as schemes and charts contributes to the situation development. Special attention is paid to the character of supporting teaching resources which determine the content of students’ independent work in the process of preliminary planning and further development of group communication. A variety of methods of students’ independent work while preparing for the discussion of a certain problem are emphasized. The stages of work are distinguished, the types of work are determined, different types of texts are given. It is stated that to acquire the skills of problematic questions discussion it is necessary to do special exercises in which the means of making sayings, formulating evaluation arguments, set expressions would be digested and which contributes to the development of students’ language abilities. Conversation all topics in which enhancement of communications kills is trained are given as examples. The importance of usage of the problem solving method which contributes to the development of communication skillsand allows to model communication in different situations is shown.